Surface modification of electrospun ABS/ENR blend membranes using polyvinyl alcohol-citric acid coating - Abd Manaf, Mohd Edeerozey; Shueb, Mohammed Iqbal; Mohamed, Mahathir; Mohamad, Ahmad Nubly; Alkaseh, Adel M. Ali (Penerbit Akademia Baru, 2024)
Polymeric membranes, designed for selective permeability to efficiently separate oil from water, present an innovative solution for oil-water separation and offer a rapid and environmentally friendly response to spill incidents. In this study, micro-nanofiber membranes are fabricated using acrylonitrile-butadiene-styrene (ABS) and its blend with epoxidized natural rubber (ENR) using electrospinning method. The electrospun fiber membranes are then coated with polyvinyl alcohol (PVA) containing various concentrations of citric acid (CA), to investigate the impact of PVA coating variations on the physical and mechanical properties of the ABS/ENR membranes. It was found that mechanical properties of the ABS/ENR membrane are superior to that ABS membrane, as demonstrated by higher values of tensile strength and modulus. ENR rubber introduces elasticity and flexibility to the rigid ABS, which leads to enhanced mechanical properties. Addition of ENR was also found to improve hydrophobicity of the membrane as demonstrated by the increase in contact angle. The inclusion of CA was observed to have a beneficial impact on the strength and toughness of the ABS/ENR membrane. The presence of CA promotes the hydrophilic property in both the ABS and ABS/ENR membranes. A finer and more uniform strands were observed for ABS/ENR membranes than ABS membranes, which reflects their higher tensile strength values. From this study, it can be concluded combination of electrospinning and coating method is efficient in producing porous membranes with tailored hydrophobic/hydrophilic property crucial for efficient oil-water separation.